Artificial Intelligence in Strategic Management: A Systematic Literature Review - Suprasman Suprasman; Novelma Lastri; Variza Aditiya; Dwi Hartutik; Said Mustafa (Smart Education, 2026)
Abstract: The rapid advancement of Artificial Intelligence (AI) has transformed the way organizations formulate strategies, make decisions, and create competitive advantages. AI implementation is no longer limited to business process automation but also supports data analytics, market forecasting, product innovation, and strategic decision-making. Nevertheless, organizations continue to face significant challenges in adopting AI, including organizational readiness, workforce competencies, data governance, and ethical concerns. This study aims to synthesize the existing literature on AI implementation in strategic management through a Systematic Literature Review (SLR). Relevant scholarly articles were collected from Scopus, Web of Science, and Google Scholar based on predefined inclusion criteria. The review focuses on theoretical developments, organizational benefits, implementation challenges, critical success factors, and future research directions. The findings indicate that AI significantly enhances strategic decision-making, operational efficiency, business innovation, and organizational competitiveness. However, successful AI implementation depends on organizational readiness, digital leadership, data quality, and human resource capabilities. This review contributes by providing a comprehensive conceptual synthesis of AI in strategic management and identifying promising directions for future research. Keywords: Artificial Intelligence, Strategic Management, Digital Transformation, Decision Making, Systematic Literature Review. Abstrak: Perkembangan kecerdasan buatan (Artificial Intelligence atau AI) telah mengubah cara organisasi merumuskan strategi, mengambil keputusan, dan menciptakan keunggulan kompetitif. Implementasi AI tidak lagi terbatas pada otomatisasi proses bisnis, tetapi juga mendukung analisis data, prediksi pasar, inovasi produk, serta peningkatan efektivitas pengambilan keputusan strategis. Meskipun demikian, implementasi AI dalam manajemen strategis masih menghadapi berbagai tantangan, seperti kesiapan organisasi, kompetensi sumber daya manusia, tata kelola data, serta aspek etika penggunaan teknologi. Penelitian ini bertujuan untuk mensintesis perkembangan penelitian mengenai penerapan AI dalam manajemen strategis melalui pendekatan Systematic Literature Review (SLR). Artikel ilmiah yang dianalisis diperoleh dari basis data Scopus, Web of Science, dan Google Scholar berdasarkan kriteria inklusi yang telah ditetapkan. Analisis difokuskan pada perkembangan konsep, manfaat, tantangan implementasi, faktor keberhasilan, serta arah penelitian di masa depan. Hasil sintesis menunjukkan bahwa AI memberikan kontribusi signifikan terhadap peningkatan kualitas pengambilan keputusan, efisiensi operasional, inovasi bisnis, dan keunggulan kompetitif organisasi. Namun, keberhasilan implementasi AI sangat dipengaruhi oleh kesiapan organisasi, kepemimpinan digital, kualitas data, serta pengembangan kompetensi sumber daya manusia. Penelitian ini memberikan kontribusi konseptual berupa pemetaan perkembangan kajian AI dalam manajemen strategis serta mengidentifikasi peluang penelitian selanjutnya. Kata kunci: Artificial Intelligence, Strategic Management, Digital Transformation, Decision Making, Systematic Literature Review.